The short- and long-run inconsistency of the expansionary austerity theory: A post-Keynesian/evolutionist critique - Alberto Botta (Levy Economics Institute of Bard College, 2016)
This paper provides a critical analysis of expansionary austerity theory (EAT). The focus is on the theoretical weaknesses of EAT-the extreme circumstances and fragile assumptions under which expansionary consolidations might actually take place. The paper presents a simple theoretical model that takes inspiration from both the post-Keynesian and evolutionary/institutionalist traditions. First, it demonstrates that well-designed austerity measures hardly trigger short-run economic expansions in the context of expected long-lasting consolidation plans (i.e., when adjustment plans deal with remarkably high debt-to-GDP ratios), when the so-called "financial channel" is not operative (i.e., in the context of monetarily sovereign economies), or when the degree of export responsiveness to internal devaluation is low. Even in the context of non-monetarily sovereign countries (e.g., members of the eurozone), austerity's effectiveness crucially depends on its highly disputable capacity to immediately stabilize fiscal variables. The paper then analyzes some possible long-run economic dynamics, emphasizing the high degree of instability that characterizes austerity-based adjustments plans. Path-dependency and cumulativeness make the short-run impulse effects of fiscal consolidation of paramount importance to (hopefully) obtaining any appreciable medium-to-long-run benefit. Should these effects be contractionary at the onset, the short-run costs of austerity measures can breed an endless spiral of recession and ballooning debt in the long run. If so, in the case of non-monetarily sovereign countries debt forgiveness may emerge as the ultimate solution to restore economic soundness. Alternatively, institutional innovations like those adopted since mid-2012 by the European Central Bank are required to stabilize the economy, even though they are unlikely to restore rapid growth in the absence of more active fiscal stimuli.
Keywords: E12; E61; E62; 330; Fiscal Policy; Expansionary Austerity Theory; Post-Keynesian Macro Models